Buffer-aided half-duplex relaying can outperform ideal full-duplex relaying - Zlatanov, Nikola; Schober, Robert (IEEE Communications Letters, 2013)
We consider a three-node relay network comprised of a source, a relay, and a destination, and compare the throughputs of ideal full-duplex (FD) and half-duplex (HD) relaying. For FD relaying, we assume that the relay uses half of its antennas for reception and the other half for transmission. In contrast, for HD relaying, the relay uses all of its antennas for either reception or transmission and a buffer for data storage. Our results show that if the numbers of antennas at source and destination are equal to or larger than the number of antennas at the relay, HD relaying may achieve a similar, and in some cases even higher, throughput compared to ideal FD relaying. © 1997-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: buffer-aided; full-duplex; Half-duplex; relaying